The role and activities of custodians of aristocratic collections in Bohemia in the 19th century and first half of the 20th century - Radostová, Šárka (Acta historiae artis Slovenica, 2023)
In a number of European countries, entrusting the care of the extensive sets of collections owned by aristocrats to a special employee or employees had been customary since the Renaissance. The focus of this study is the period from the beginning of the 19th century to the end of the Second World War. Selected individuals who together represent approximately one hundred and fifty years of care for collections located in aristocratic residences are presented. The academy-trained painter František Horčička, the former town executioner Carl Huss and the husband-and-wife team Wilhelmina and Karl Vincenz Auersperg devoted themselves to collections in the 19th century, while professor Josef Schmoranz and lawyer Josef Polák did so in the first half of the 20th century.
Keywords: aristocracy; aristocratic collections; aristokracija; art collections; Auerspergi; Carl Huss; custodians of art collections; Czechia; František Horčička; inventarji umetnostnih zbirk; inventories of art collections; Josef Polák; Josef Schmoranz; Karl Vincenz Auersperg; Metternich, Klemens Wenzel Nepomuk Lothar von; plemiške zbirke; Rudolf Josef Colloredo-Mannsfeld; skrbniki umetnostnih zbirk; umetnostne zbirke; Wilhelmina Auersperg